(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Doris Lessing’s short stories “Little Tembi” and “No Sale for Witchcraft” are profound explorations of cultural identity, racial prejudice, and social conflict, rendered through rich symbolic imagery.